Physician’s Knowledge of Appropriate Prescribing for the Elderly—A Survey Among Family and Internal Medicine Physicians in Nigeria - Fadare, Joseph O.; Obimakinde, Abimbola Margaret; Enwere, Okezie O.; Desalu, Olufemi O.; Ibidapo, Raphael Olasoji (Frontiers in Pharmacology, 2019)
Background Prescription and use of inappropriate medications have been identified as a major cause of morbidity among the elderly. Several screening tools have been developed to identify inappropriate medications prescribed for elderly patients. There is dearth of information about the knowledge of Nigerian physicians regarding these screening tools and appropriate prescribing for the elderly in general. The primary objective of this study was to assess the knowledge of Nigerian physicians about these screening tools and appropriate prescribing of medications for the elderly. Methods The study was a cross-sectional questionnaire-based study conducted among physicians working in Family Medicine and Internal Medicine departments of four tertiary healthcare facilities in Nigeria. The questionnaire consisted of sections on general characteristics of respondents and their knowledge of four selected screening tools for inappropriate medications in the elderly. Ten clinical vignettes representing different therapeutic areas (using the best option type questions) about medicine use in the elderly were included with a score of one and zero for correct and wrong answers respectively. The knowledge of respondents was classified as (total score over 10): poor (score <5), average (score 5-6) and good (score 7-10) Results One hundred and five physicians returned completed questionnaires. Twenty percent of respondents knew about Beers criteria while 15.6% were familiar with the STOPP criteria. Majority (83; 84.7%) of the respondents were confident of their ability to prescribe appropriately for elderly patients. The mean knowledge score was 5.3 ±2.0 with 32 (30.5%), 41 (39%) and 32 (30.5%) having low, average and good scores respectively. The association between the knowledge score, duration of practice and seniority was statistically significant (OR: 3.6 (p =.004) and OR: 3 (p = .012) respectively. Conclusion There are significant gaps in the knowledge of Nigerian physicians about screening tools for inappropriate medications. There is a need for stakeholders involved in the care of elderly Nigerian patients to develop new strategies to improve services being offered. These may include introduction of modules on appropriate prescribing in the curriculum of undergraduate and postgraduate medical education and the routine use of some screening tools for inappropriate medications in daily clinical practice.